How I learned to understand the world : a memoir - Rosling, Hans; Härgestam, Fanny (Flatiron Books, 2020)
The late WHO advisor, co-founder of Sweden's Doctors Without Borders traces his remarkable career spent in environments ranging from an emergency clinic in Mozambique to the World Economic Forum at Davos.